Process evaluation of a community-based adolescent obesity prevention project in Tonga - Pomana Siosifa; Mavoa Helen M; Moodie Marj M; Fotu Kalesita F; Schultz Jimaima T; Swinburn Boyd A (BMC, 2011)
Abstract Background The rising burden of obesity in Tonga is alarming. The promotion of healthy behaviours and environments requires immediate urgent action and a multi-sectoral approach. A three-year community based study titled the Ma'alahi Youth Project (MYP) conducted in Tonga from 2005-2008 aimed to increase the capacity of the whole community (schools, churches, parents and adolescents) to promote healthy eating and regular physical activity and to reduce the prevalence of overweight and obesity amongst youth and their families. This paper reflects on the process evaluation for MYP, against a set of Best Practice Principles for community-based obesity prevention. Methods MYP was managed by the Fiji School of Medicine. A team of five staff in Tonga were committed to planning, implementation and evaluation of a strategic plan, the key planks of which were developed during a two day community workshop. Intervention activities were delivered in villages, churches and schools, on the main island of Tongatapu. Process evaluation data covering the resource utilisation associated with all intervention activities were collected, and analysed by dose, frequency and reach for specific strategies. The action plan included three standard objectives around capacity building, social marketing and evaluation; four nutrition; two physical activity objectives; and one around championing key people as role models. Results While the interventions included a wide mix of activities straddling across all of these objectives and in both school and village settings, there was a major focus on the social marketing and physical activity objectives. The intervention reach, frequency and dose varied widely across all activities, and showed no consistent patterns. Conclusions The adolescent obesity interventions implemented as part of the MYP program comprised a wide range of activities conducted in multiple settings, touched a broad spectrum of the population (wider than the target group), but the dose and frequency of activities were generally insufficient and not sustained. Also the project confirmed that, while the MYP resulted in increased community awareness of healthy behaviours, Tonga is still in its infancy in terms of conducting public health research and lacks research infrastructure and capacity.